Free Movement of Legal Professionals within the European Union - Una Særún Jóhannsdóttir 1982- (2009)
The EC Treaty has as its main goal the creation of a single market for all economic activities within the European Community. For this purpose it set up a system for persons to move freely within the Union with the introduction of rules on free movement of workers, services and establishment. To reach the goal of free movement of persons the professions within the Community had to be liberalized from unjustified national rules which prevented persons from providing cross border services or establishing in other Member States. One of these professions was the legal profession. Consequently, in principle, all fully qualified European lawyers have a right to practice law in other Member States, either by providing temporary services or by becoming established. This thesis focuses on the development towards creating an effective system of free movement for legal professionals within the European Union. Is there really a single European market for lawyers or are lawyers on the move still met with obstacles? In order to answer that question the thesis makes a survey of the evolution of EC law focusing on legal professionals. Beginning with considering the nature of the Treaty provisions on freedom to provide services (Article 49 EC) and the freedom of establishment (Article 43) which are the means by which lawyers derive their right to free movement. Furthermore, the Directives created to facilitate lawyers´ free movement are thoroughly examined. These pieces of legislation form the system for lawyers´ free movement. A system which would probably not have seen the light of day if it were not for the European Court of Justice and it’s dynamic and progressive interpretation of Treaty Articles governing lawyers free movement. Therefore, the Court´s interpretation and role in the development play a key role in the analysis of the subject. After establishing what rules are applicable to lawyers and what rights they have when practising law across borders, the implementation of the rules in Iceland and Sweden will be ...